Studi Analisis Penilaian Kinerja Dengan Metode Balanced Scorecard Pada CV. Langgeng Abadi Body Repair - Ugroseno Damara Prasadhana Handoyo; Wahyu Junaedi; Dede Pebrianto (Journal of Economic, Bussines and Accounting (COSTING), 2022)
The Balanced Scorecard is used by companies to measure their performance as a more comprehensive measurement tool or technique because it uses two parameters, namely financial and non-financial. The industrial management method with the Balanced Scorecard approach is very easy to apply, even to small home industries because it does not require a fee. The application of management methods with the Balanced Scorecard analysis approach in small and medium-sized industries can see all aspects that can affect the profit and sustainability of the company. And in the end, the company was able to develop its industry on a much larger scale. Keywords: company performance appraisal, Balanced Scorecard method